One-Pot Synthesis of Bio-based Styrenes from β-(Phenyl)-β-(phenylthio)propionic Acids via Neutral Ionic Liquid, Microwave Irradiation Triggered Cascade Decarboxylative Dehydrosulfenylation - Singh, Richa; Rastogi, Sumit K.; Kumar, Santosh; Equbal, Danish; Thopate, Yogesh; Sinha, Arun K. (Synthesis, 2025)
A direct, new and eco-friendly strategy for the one-step synthesis of methoxylated and hydroxylated styrenes from β-(phenyl)-β-(phenylthio)propionic acids is reported. This approach utilizes a neutral ionic liquid [hmim]Br-triggered cascade decarboxylative dehydrosulfenylation reaction under microwave irradiation, without the need for strong bases, acids and toxic metal oxidants, and eliminates the need for a phenolic group protection–deprotection strategy, thus offering an efficient route to bio-based commercially important FEMA GRAS approved vinylphenols. NMR studies suggest a concerted reaction mechanism.
Keywords: ionic liquids; microwave irradiation; deprotected; decarboxylative dehydrosulfenylation; styrenes